2007
DOI: 10.1093/pcp/pcm081
|View full text |Cite
|
Sign up to set email alerts
|

A GUS/Luciferase Fusion Reporter for Plant Gene Trapping and for Assay of Promoter Activity with Luciferin-Dependent Control of the Reporter Protein Stability

Abstract: A gene-trapping vector carrying a GUS/Luciferase dual reporter gene was developed to establish an efficient and convenient screening system for T-DNA-based gene trapping in plants. A key feature of this gene trap scheme is to place two different types of reporters, luciferase (Luc) and beta-glucuronidase (GUS), as a fusion protein within a trapped gene to probe the activity of the gene. Luc is then utilized as a non-invasive, vital and highly sensitive screening reporter to identify trapped lines, including di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 36 publications
0
37
0
Order By: Relevance
“…Expression was controlled by the 35Spro as above. As GUS enzyme activity reflects well GUS protein levels (Koo et al, 2007), the translation efficiency was estimated by determining the ratio of GUS activity and GUS mRNA expression in leaves of three independent transgenic events each (Fig. 5B).…”
Section: Translation Inhibition In Vitro and Effect On Reporter Gene mentioning
confidence: 99%
“…Expression was controlled by the 35Spro as above. As GUS enzyme activity reflects well GUS protein levels (Koo et al, 2007), the translation efficiency was estimated by determining the ratio of GUS activity and GUS mRNA expression in leaves of three independent transgenic events each (Fig. 5B).…”
Section: Translation Inhibition In Vitro and Effect On Reporter Gene mentioning
confidence: 99%
“…The frequency of gus gene transcription fusion and gus gene expression in different plant tissues was higher [42]. Koo et al [43] revealed 13 % of gene trapping efficiency and Yamamoto et al [44] reported the same result for promoterless trapping vectors and 41 % of gene trapping efficiency for IRES-type trapping vector. We note that in our studies, however, enormous for promoter tagging experiments number of transgenic plants was resistant to PPT.…”
Section: Lox Sites Of the Cre/lox Recombination System From Bacteriopmentioning
confidence: 94%
“…For a gene to be selected as a reporter, it must be able to easily detect signals secreted by the expressed reporter gene in the cells [30]. The lux gene derived from bacteria, and luciferase from the firefly and click beetle (luc), are two other common reporter genes used in bioluminescence imaging.…”
Section: Fluorescent Reporters and Their Applications For In Vivo Imamentioning
confidence: 99%
“…pTRKH3 is a shuttle vector for E. coli, Enterococcus, Lactococcus, Streptococcus and Lactobacillus [60]. The vector has a copy number (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) in E. coli, and a somewhat higher copy number in Lactococcus and Streptococcus species [64]. It carries a gene for erythromycin resistance, which is expressed in E. coli and LAB.…”
Section: Fluorescent Reporters and Their Applications For In Vivo Imamentioning
confidence: 99%